Improving the Volumetric Capacity of Gallocyanine Flow Battery by Adding a Molecular Spectator - Martínez-González, Eduardo; Peljo, Pekka (American Chemical Society, 2025)
Gallocyanine (GAL) was recently introduced as a promising aqueous-soluble electroactive molecule for preparing two-electron storage alkaline flow battery (FB) negolytes. The development of a cost-effective GAL FB electrolyte is limited by the unexpectedly low solubility of GAL. In this work, the compound 7-amino-4-hydroxy-2-naphthalenesulfonic acid was introduced as a molecular spectator to modulate the solubility of GAL in KOH; this formulation allowed the preparation of a negolyte with a theoretical volumetric capacity of 32.00 Ah L–1. The cycling stability of an improved GAL electrolyte was demonstrated by operating a FB cell outside of the glovebox (bubbling N2 in the tanks). The cell exhibited a Coulombic efficiency close to 98\% and began operating with 72.1\% of its theoretical capacity (16.06 Ah L–1), retaining 88\% of it after 110 cell cycles. This work demonstrates that significant improvement in electrolyte performance can be obtained with suitable additives and electrolyte engineering.